2015
DOI: 10.1111/pai.12414
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bronchiolitis, recurrent wheezing, and related hospitalization in preterm infants during the first year of life

Abstract: In this study, several non-modifiable parameters (family history of asthma, low birthweight, need for mechanical ventilation) and modifiable parameters (young maternal age, DCA, or exposure to school-age siblings) were identified as significant risk factors for the development of bronchiolitis and recurrent wheezing during the first year of life in MLP infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
3
18
0
2
Order By: Relevance
“…Fifteen pediatric hospitals in Spain participated in the study (Table ). Interim results for the first year have been previously reported, and the complete data for the study including the second and third years are included in the present report. The study protocol was approved by the Ethics Committees, and all the procedures followed the principles outlined in the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…Fifteen pediatric hospitals in Spain participated in the study (Table ). Interim results for the first year have been previously reported, and the complete data for the study including the second and third years are included in the present report. The study protocol was approved by the Ethics Committees, and all the procedures followed the principles outlined in the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%
“…More recent analysis from a large population based, data-linkage study reported a 12% increase in the overall frequency of infection-related hospitalisation during childhood for each week reduction in gestational age [6]. In addition to reduced gestational age, low birth weight, although at least partly inter-dependent with gestational age, has also been attributed to a 19% increase in the proportion of infants hospitalised with acute respiratory infection for each 500 g reduction in birth weight [6,41]. …”
Section: Viral Infection Requiring Readmission In Early Lifementioning
confidence: 99%
“…Infants colonized with Clostridium difficile were found to be at higher risk for developing eczema, recurrent wheeze, and allergic sensation, while Escherichia coli was associated with eczema (Penders et al, ). Low birth weight is one of the risks for development of both bronchiolitis and asthma in the first year of life (Perez‐Yarza et al, ). In a study of 432 children with parental history of atopy, the odds ratio for development of asthma in those children born by Cesarean was 2.1 (Pistiner et al, ).…”
Section: Part IImentioning
confidence: 99%